NOTES ON RESUPINATE HYMENOMYCETES-I On Pellicularia Cooke - M. A. DONK (BRIN Publishing (Penerbit BRIN), 1954)
The author concludes that Pellicularia Cooke is to be regarded as the name of an inseparable mixtum compositum (nomen confusum) and hence as illegitimate (impriorable).He believes that, apart from a hypothetical gelatinous medium,Cooke's original material consisted of the combination of the vegetative hyphae of a resupinate hymenomycete and the spores of a pervading imperfect fungus. If one of these constituent elements were to be selected as type, the choice would be the spores rather than the vegetative byphae selected by Rogers.